2020
DOI: 10.1186/s12987-020-00188-2
|View full text |Cite
|
Sign up to set email alerts
|

Angiomodulin (IGFBP7) is a cerebral specific angiocrine factor, but is probably not a blood–brain barrier inducer

Abstract: Background: Several secreted factors have been identified as drivers of cerebral vasculature development and inducers of blood-brain barrier (BBB) differentiation. Vascular endothelial growth factor A (VEGF-A) is central for driving cerebral angiogenesis and Wnt family factors (Wnt7a, Wnt7b and norrin) are central for induction and maintenance of barrier properties. Expressed by developing neural tissue (neuron and glia progenitors), they influence the formation of central nervous system (CNS) vascular network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…However, the cell-cell communication between VECs and pancreatic resident cells remain largely unexplored. In other organs, such as bone marrow, brain and liver, VEC release several angiocrine factors to target the tissue resident cells to mediate organ development and regeneration (43)(44)(45)(46)(47). Hematopoietic stem/progenitor cells, astrocyte and cardiomyocyte derived signals are reported to induce differentiation of VEC and angiogenesis (17,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…However, the cell-cell communication between VECs and pancreatic resident cells remain largely unexplored. In other organs, such as bone marrow, brain and liver, VEC release several angiocrine factors to target the tissue resident cells to mediate organ development and regeneration (43)(44)(45)(46)(47). Hematopoietic stem/progenitor cells, astrocyte and cardiomyocyte derived signals are reported to induce differentiation of VEC and angiogenesis (17,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…In a new study in 2021, IGFBP7 was reported to be related to lipid metabolism in nonalcoholic fatty liver disease (NAFLD) [ 55 ]. In addition, it is also involved in the development of a variety of brain diseases [ 98 100 ]. In our results, IGFBP7 showed a negative correlation with figure copy scores, indicating that IGFBP7 might be related to visuospatial/constructional dysfunction in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP7 is highly expressed in the vasculature during development in the central nervous system. But, in adults, the IGFBP7 expression was reported to be only restricted to smooth muscle cells covering large vessels and choroid plexus vasculature, which is characterized by limited BBB property and high permeability ( Hooper et al, 2009 ; Bar et al, 2020 ). Increased IGFBP7 expression in vasculature was observed in brain pathological conditions including glioblastoma and stroke, as well as other types of tumors ( Hooper et al, 2009 ; Dieterich et al, 2012 ; Buga et al, 2014 ; Komiya et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%